PEMANFAATAN APLIKASI ENGLISH PRONOUNCER UNTUK PENGAJARAN MATA KULIAH SPEAKING I MAHASISWA SEMESTER II PRODI PENDIDIKAN BAHASA INGGRIS STKIP YPM BANGKO - Diyan Andriani; Sri Utaminingsih (Jurnal Muara Pendidikan, 2022)
The speaking ability of first semester students with good pronunciation was still low. Therefore, in Semester II there needs to be an effort to overcome this problem, namely by using mobile learning based on Android smartphones using the "English Pronouncer" application. The purpose of this study was to obtain the results and implementation of the speaking I teaching process using the English Pronouncer application. This research is a Classroom Action Research with research stages including: (1) Action Plan; (2) Implementation of the planned Action with three cycles; (3) Data collection and (4) Data Analysis. The results showed that in the first cycle the average score was 61.66 with complete students (achieving a score of 75) were 5 students out of a total of 15 students or 33.33%. In the second cycle the average score increased to 74.44 followed by an increase in completeness to 7 students or 46.66%. In the third cycle, the average score increased again to 97.22 with 14 students who completed a total of 15 students or 93.33%. In line with the increase in score, there was a decrease in pronunciation errors from cycle I to cycle II and III. Based on the results of the study, it can be concluded that the use of the English pronouncer application for teaching speaking I courses can improve students' speaking skills.